Migration Policy: Lessons from Cooperatives - Margit Osterloh; Bruno S. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2017)
We propose an immigration policy based the model of cooperatives. Incoming migrants have to acquire a participation certificate. In exchange, the immigrants may enter the country of choice without danger. The revenue goes to the country of the recipient nation rather than to human smugglers. The cost would be much lower than today's efforts to secure the borders. Asylum seekers get back the money paid for the certificate. Immigration is therewith regulated more efficiently than today. Not all entrance barriers and coercive measures to prevent illegal entry would disappear. However, the pressure of illegal migrants is strongly reduced.
Keywords: D71; F22; F66; J46; J61; 330; Immigration; asylum; cooperatives; participation certificates; borders